Numerical Study on Heat Transfer and Pressure Drop in a Mini-Channel with Corrugated Walls - Begag, Abdelaziz; Saim, Rachid; Öztop, Hakan Fehmi; Abboudi, Said (Shahid Chamran Univ Ahvaz, Iran, 2021)
This study presents the numerical results relative to the development of heat transfer and pressure drop inside a corrugated channel, under constant heat flux conditions applied to the walls; the working fluid is air. The test section is a channel with two plates having trapezoidal-shaped corrugations with V-folds. The corrugated plates were placed inside a 12.5 m high channel and tested for three different inclination angles, i.e. 20 degrees, 40 degrees and 60 degrees. The model was simulated for a heat flux of 0.58 kW /m2, while the Reynolds numbers were considered within the interval ranging from 600 to 1400. The standard turbulent model (k-epsilon) was employed to simulate the flow and heat transfer developments within the channel. In addition, the governing equations were solved using the finite volume method in a structured uniform grid arrangement. Moreover, the effects of the geometric parameters on heat transfer and flow evolution were discussed as well. It is also worth noting that the corrugated surface had a significant impact on the enhancement of heat transfer and pressure drop due to breakage and destabilization occurring in the thermal boundary layer.
Keywords: Forced flow; Laminar; Turbulent; Numerical; Heat exchanger